Cages - McKean, Dave 1963- (Dark Horse Books, 2010)
"Cages tells the story of three artists: Leo Sabarsky, a painter in need of inspiration; Angel, a nightclub musician who seems oblivious to the adulation of his fans; and Jonathan Rush, a writer whose novel Cages so enraged his readers that he now lives in captivity. How these characters break free of their mental cages forms the central conflict of this book, which evolves into a meditation on creativity and godhood."--Library Journal
"This volume collects Cages numbers one through ten, originally published by Tundra and Kitchen Sink Press between 1990 and 1996, along with additional materials published by Kitchen Sink Press in the Cages hardcover edition, 1998"--Preliminary page
Keywords: Inspiration; Kreativität; Autor; Künstler; Musiker; Comic